THE QUALITY OF SELECTED SOUTH AFRICAN AND INTERNATIONAL HOMOEOPATHIC MOTHER TINCTURES - Scheepmaker, Mandé Michelle; Gower, Neil Travis (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
The high potential variability of chemical composition of the plant material involved in the manufacture of homoeopathic mother tinctures (a common source of homoeopathic medicines), renders both their quality control and assurance a significant challenge (Pande and Pathak, 2006). The absence of significant regulations regarding the quality of Complementary and Alternative Medicines (CAM) in South Africa contributes to this challenge (Gqaleni et al, 2007). In order to assess any quality differences between local and international manufacturers, the following homoeopathic mother tinctures, Artemisia absinthium, Rosmarinus officinalis e foliis recentibus, Salvia officinalis and Sambucus nigra, were chosen on the basis that they can be grown both locally in South Africa and internationally and are prepared according to the German Homoeopathic Pharmacopoeia (GHP), method 3a. Colour analysis was followed by thin layer chromatographic (TLC) analysis on each selected sample and relevant reference sample using both aluminum-backed TLC plates and glass-backed HPTLC plates. Photographs were taken of the resultant chromatograms, active components were identified, comparisons to the reference chromatograms were made and the overall quality of each homoeopathic mother tincture deduced. The quality of all nine of the selected samples manufactured internationally complied with the minimum quality standards set by the GHP. Five out of the six local samples complied with the minimum standards of the GHP.Notwithstanding the minimum GHP standards, the superior number of high quality international samples implies that their quality exceeded that of the locally manufactured tinctures. Greater regulation regarding the quality of these types of products has therefore been identified.